An experimental determination of the disinfection properties of the «Anolit KRYSTAL» - Мельничук, В. В. (Scientific Progress & Innovations, 2017)
The results of investigations of disinvasive activity of disinfectant «Anolit KRYSTAL» in the test cultures of eggs Ascaris suum, Trichuris ovis, Trichuris skrjabini and Trichuris globulosa, based on disinvasive efficiency (DE) are given. It has been experimentally established that the disinfectant possesses pronounced disinfestation properties in respect of experimental test cultures; A. suum – in breeding 1:3, 1:2, 1:1 and in concentrated form for all exposures (DE – 90,53–100,00 %); T. ovis – in dilution 1:2 at exposure of 60 minutes, 1:1 and in concentrated form for all expositions (DE – 94,85–100,00 %); T. skrjabini – in dilution 1:3 at exposure of 30 and 60 minutes, 1:2, 1:1 and in concentrated form for all exposures (DE – 92,31–100,00 %); T. globulosa – in breeding 1:3; 1:2; 1: 1 and concentrated form for all expositions (DE – 94,38–100,00 %).